TRANSLATION OF OCCASIONALISMS IN MEDIA TEXTS: PHILOLOGICAL ASPECT - Maksymchuk, Zhanna (Mountain School of Ukrainian Carpaty, 2022)
The aim of the study is to examine the functioning and translation of English occasionalisms into Ukrainian and vice versa in the media texts, namely a social media site Instagram. Information and explanatory functions, which are the subject of the whole article, are only its secondary purpose. Communicative-pragmatic and functional features of social networks are investigated and we analyze which translational transformations are the best to be used in a specific situation to achieve the goal, namely to influence the audience and be conducive to manipulating consciousness for useful purposes. The article presents an analysis of the fundamental aspects of the translation of occasionalisms, their structuralgrammatical and lexical functions. As a result of studying the term “occasionalism”, the following main methods of its formation are distinguished: affixal method (prefix and suffixal methods), composite, conversion, reduction, inverse derivation, fusion, borrowing from other languages and abbreviation. Also the following main methods of translating occasionalisms are distinguished: functional replacement, transcription, transliteration, descriptive translation (explication), reduction, expansion and borrowing. In addition to this, we have assumed the main translation teaching methods of occasionalisms namely cognitive and audio-visual methods. The cognitive method is aimed at forming the future translator's cognitive skills, which make it possible to determine the type and purpose of information, to highlight its main content, to build ways of solving problems while translating these lexical units, to be able to form them, to have some judgments and to show creativity. The audiovisual teaching method can be used to build and test models of translation competencies that determine the knowledge and cognitive components necessary for effective translation work. In addition, key aspects have found their way into translator training profiles and quality standards for translation services. Central to the acquisition of translation competence is reflection on decisions and actions during the translation process, as well as various process studies.